Present status of microstructured semiconductor neutron detectors - McGregor, Douglas S.; Bellinger, Steven L.; Shultis, J. Kenneth (My University, 2013)
Semiconductor diode detectors coated with neutron reactive materials have been investigated as neutron detectors for many decades, and are fashioned mostly as planar diodes coated with boron-10 ([superscript 10]B), lithium-6 fluoride ([superscript 6]LiF) or gadolinium (Gd). Although effective, these detectors are limited in efficiency (the case for boron and LiF coatings) or in the ability to distinguish background radiations from neutron-induced interactions (the case for Gd coatings). Over the past decade, a renewed effort has been made to improve diode designs to achieve up to a tenfold increase in neutron detection efficiency over the simple planar diode designs. These new semiconductor neutron detectors are fashioned with a matrix of microstructured patterns etched deeply into the substrate and, subsequently, backfilled with neutron reactive materials. Intrinsic thermal-neutron detection efficiencies exceeding 40% have been achieved with devices no thicker than 1 mm while operating on less than 5 volts.
Keywords: Semiconductor neutron detectors; Solid state neutron detectors